Nicotine Deprivation Influences P300 Markers of Cognitive Control - Evans, David E (Nature Publishing Group, 2013)
Studies suggest that reduced cognitive control due to nicotine withdrawal may have a critical role in promoting tobacco use. The P3 family of event-related brain potential (ERP) components is thought to serve as markers of cognitive control processes. Unfortunately, existing research that examines the effects of nicotine deprivation on P3 amplitude has been marred by small sample sizes and other design limitations. The present study sought to determine the effects of nicotine deprivation on P3b and P3a amplitudes, which index task relevant target detection and orienting responses to novelty, respectively. A secondary aim was to examine self-reported trait cognitive control as a moderator of nicotine deprivation-induced reductions in P3b and P3a amplitudes. In all, 121 nicotine-dependent smokers attended two experimental sessions following 12-h smoking/nicotine deprivation. In a counterbalanced manner, participants smoked nicotine cigarettes during one session and placebo cigarettes during the other session. Findings indicated that nicotine deprivation reduced P3b amplitude (p<0.00001) during a three-stimulus oddball task independent of trait cognitive control. In contrast, nicotine deprivation reduced P3a only among participants who scored lower on measures of trait cognitive control. Implications for conceptualizing risk for nicotine dependence, and its treatment, are discussed.